Coronavirus Disease-19 Infection: Implications on Male Fertility and Reproduction - Navarra, Annalisa; Albani, Elena; Castellano, Stefano; Arruzzolo, Luisa; Levi-Setti, Paolo Emanuele (Frontiers in Physiology, 2020)
The pandemic caused by Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) has led to several concerns on male fertility. Nowadays, there are numerous unanswered questions, for example: is the virus present or not in the seminal fluid of infected subjects? Could the seminal fluid represent a way of sexual transmission for the virus? Why do men appear to be more susceptible than women? Several studies have been carried out to ascertain the presence of SARS−CoV−2 in the seminal fluid, with contrasting results; the expression of angiotensin-converting enzyme-2 (ACE2) and transmembrane serine protease 2 (TMPRSS2) in the testes and in the male genital tract led to speculation about the possible presence of the virus in the seminal fluid. However, it was found that ACE2 and TMPRSS2, used by the virus to enter host cells, are expressed differently in certain testicle cells (stem germ cells, Leydig and Sertoli cells), yet the testicle cells in which ACE2 and TMPRSS2 molecules are simultaneously expressed are rare. This fact would suggest that the virus is not able to enter testicular cells, that it is not present in the seminal fluid and that it cannot infect male germ cells. However, the direct influence of SARS-CoV-2 on the testes is still to be evaluated, and recent results are very controversial. SARS-CoV-2 could enter the testicle using alternative paths and lead to alterations in testicular functionality. Another plausible consideration is that the COVID-19 disease could also indirectly cause alterations to testicular activity, since the fever and the cytokinic storm generated by the immune system can lead to damage of the testicular activity, consequently compromising male fertility. Although the literature provides controversial evidence, the purpose of this review is to lend a general overview about the state of the art. Despite the lack of studies, it would represent a starting point for further investigation about the effect of this coronavirus on male fertility.